The intertextual reception of Genesis 1-3 in Irenaeus of Lyons - Presley, Stephen O. (The Bible in Ancient Christianity, 2015)
In The Intertextual Reception of Genesis 1-3 in Irenaeus of Lyons , Stephen Presley explores the intertextual nature of Irenaeus' interpretation of Genesis 1-3 by drawing on contemporary discussions on the topic. Irenaeus interprets the creation accounts, Presley argues, in continuity with the rest of the scriptural witness through a series of reading strategies including: a literary sense, prophetic fulfillment, typology, philological associations, organizational strategies, narratival arrangements, prosopological interpretation, illustrative identification, and general-to-particular reasoning. Irenaeus' perspective competes with his Gnostic interlocutors who utilize similar methods of interpretation, but fashion distinctive textual relationships between Genesis 1-3 and other texts. These reading strategies circumscribe precisely how Irenaeus' intertextual exegesis is applied to these creation texts within the integrative structure of his theological perspective.